1999
DOI: 10.1007/s005860050172
|View full text |Cite
|
Sign up to set email alerts
|

Determination of inter-spinous process distance in the lumbar spine

Abstract: IntroductionA key factor in the evaluation of lumbar spine trauma is the position of the spinous processes in relation to each other as an indication of the status of the posterior stabilising structures. More or less severe separation of the spinous processes can result in a loss of mechanical support from the posterior spinal structures, and consequently in potential instability of the injured spinal segment. The exact amount of separation of the posterior elements that indicates such an injury on convention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…Negative effects in spine fusion have been reported, including pseudoarthosis, spinal stenosis, spondylolysis and accelerated degeneration of non-fused segments [5,28,39,44,48]. The main argument to fuse in thoracolumbar spine fractures is the lack of correction noticed in surgeries without arthrodesis, which is mainly caused by the degeneration of intervertebral discs involved in the fracture [3,9,27,30,31,37,38,43], or by the presence of capsuloligamentous disruptive injuries of the posterior column [34,40,55].…”
Section: Introductionmentioning
confidence: 99%
“…Negative effects in spine fusion have been reported, including pseudoarthosis, spinal stenosis, spondylolysis and accelerated degeneration of non-fused segments [5,28,39,44,48]. The main argument to fuse in thoracolumbar spine fractures is the lack of correction noticed in surgeries without arthrodesis, which is mainly caused by the degeneration of intervertebral discs involved in the fracture [3,9,27,30,31,37,38,43], or by the presence of capsuloligamentous disruptive injuries of the posterior column [34,40,55].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, using coronal x-ray images Zucherman et al 4 observed that the ISP distances were similar in the neutral or standing position before and after X-Stop implantation (51 and 52 mm, respectively) after 12 months in 100 LSS patients with an average age of 70 years. 19 The differences among these studies might be due to different measurement methods and inclusion criteria: Elderly patients of our study had remarkable lumbar degeneration. On the other hand, the 2-dimensional image measurement technique employing plain radiograph might not be able to consistently locate the actual shortest distance of the ISP.…”
Section: Discussionmentioning
confidence: 85%
“…We propose a modified classification system in this study, adding the interspinous opening to the load-sharing classification, and creating the modified load sharing classification (MLSC). For the analysis of the posterior spinal process distance, we used the method proposed by Neumann et al [15] which quantifies the opening of the spinal processes in the posterior vertebral arch in radiographs in anterior-posterior (AP) view, taking into consideration the cranial end of the base of the spinous processes. The averages in adjacent levels were used as standards for normality.…”
Section: Methodsmentioning
confidence: 99%
“…The most used method to investigate the posterior ligament insufficiency is the analysis of the opening of the spinous processes. Based on the anteriorposterior radiographic analysis of 200 normal subjects, Neumann et al [15] defined the indirect values indicative of this failure that were accurate and reproducible among independent examiners. In clinical practice, most physicians believe that patients with increased interspinous distance have an indirect sign of biomechanical instability due to posterior spinal ligament insufficiency.…”
Section: Introductionmentioning
confidence: 99%